(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mild steel is an appealing alternative for auxiliary segments in industrial and mechanical applications because of its ease and high accessibility factors. Low carbon amalgams are anything but difficult to frame great structures. Weldability is the significant worry for joining the structural parts where it prompts micro-structure changes, variety in mechanical properties and more erosion when contrasted with a base metal. An endeavor is made to weld the base metal joining by utilizing combination welding procedures, for example, Shielded Metal Arc Welding (SMAW) and applied metal coating on the welded joint to beat the above said issues. Even though different coating materials are available, Ni-Cr is selected as coating material because of its good properties and having more elasticity. The coated weld specimen is tested for tensile strength on a universal testing machine by conducting tensile test. The tensile test results are analyzed and observed that there is an improvement in the tensile strength of the mild steel welded joints by Ni-Cr coating to a maximum thickness of 300microns on weld area when compared with non coated mild steel welded joints.